Lighting design basics - Karlen, Mark; Spangler, Christina; Benya, James
"Provides fundamental concepts and prescriptive techniques, including the latest on LEDs, in a concise, highly visual format"--Provided by publisher.
RC Songcayauon (Recommending faculty) AY 2022-2023
Includes index.
Keywords: Lighting; Lighting, Architectural and decorative; ARCHITECTURE / Interior Design / General